An Assize of Bread at Mobile, Alabama - Scroggs, William O. (Quarterly Journal of Economics, 1907)
An Assize of Bread at Mobile, Alabama Get access William O. Scroggs William O. Scroggs Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 2, February 1907, Pages 330–332, https://doi.org/10.2307/1883437 Published: 01 February 1907